Endogenous term premia and anomalies in the term structure of interest rates: explaining the predictability smile - William Roberds; Charles H. Whiteman (Federal Reserve Bank of Atlanta, 1996)
Recent studies have documented the existence of a "predictability smile" in the term structure of interest rates: spreads between long maturity rates and short rates predict subsequent movements in interest rates provided the long horizon is three months or less or if the long horizon is two years or more, but not for intermediate maturities. Accounts for portions of the smile involve interest rate smoothing by the Fed, time-varying risk premia, "Peso problems," and measurement error. We take a more nearly general equilibrium approach to explaining this phenomenon and show that despite its highly restrictive nature, the Cox-Ingersoll-Ross (1985) model of the term structure can account for the predictability smile.
Keywords: 330; Financial markets; Interest rates